Prevalence of cigarette and e-cigarette use among U.S. adults eligible for lung cancer screening based on updated USPSTF guidelines. (February 2022) - Heiden, Brendan T.; Engelhardt, Kathryn E.; Cao, Chao; Meyers, Bryan F.; Puri, Varun; Cao, Yin; Kozower, Benjamin D.
Abstract: Background: The United States Preventative Services Taskforce recently updated lung cancer screening guidelines for U.S. adults with high-risk smoking histories. This has generated a previously undescribed patient population in which the prevalence of cigarette and e-cigarette use has not been described. Methods: We performed a cross-sectional study using population-based data from the Behavioral Risk Factor Surveillance System (2017–2018). We defined lung cancer screening eligibility as adults 50–80 years old with ≥ 20 pack-year smoking history who were currently smoking or quit within the last 15 years. We assessed several smoking-related outcomes including current cigarette use, ever e-cigarette use, and current e-cigarette use among respondents. Results: Among 7541 screening-eligible adults, current cigarette use was reported by 3604 (47.8%) participants. Ever and current e-cigarette use were reported by 3003 (39.8%) and 670 (8.9%) participants, respectively. Compared to individuals who were previously eligible for screening, individuals newly eligible for screening (i.e., between 50 and 55 years old with a 20–30 pack-year smoking history) were more likely to currently smoke (aOR 1.828, 95% CI 1.649–2.026, p < 0.001). While newly eligible respondents were more likely to report a history of ever using an e-cigarette (aOR 1.144, 95% CI 1.034–1.266, p = 0.009), current e-cigarette use was similar in this group compared to those individuals who were previously screening-eligible (aOR 1.014, 95% CI 0.844–1.219, p = 0.88). Conclusions: Cigarette and e-cigarette exposure are common among U.S. adults who are eligible for lung cancer screening. Expanded USPSTF criteria will capture a patient population with greater exposure to both of these products. Graphical Abstract: ga1 Highlights: The USPSTF recently expanded lung cancer screening eligibility. Rates of cigarette and e-cigarette use among newly eligible patients are undescribed. Current smoking was reported by 47.8% of screening-eligible participants. Ever and current e-cigarette use were reported by 39.8% and 8.9% of participants, respectively. Individuals newly eligible for screening were more likely to use these products.